1995
DOI: 10.1126/science.7809610
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Tests of the Roles of Adaptation, Chance, and History in Evolution

Abstract: The contributions of adaptation, chance, and history to the evolution of fitness and cell size were measured in two separate experiments using bacteria. In both experiments, populations propagated in identical environments achieved similar fitnesses, regardless of prior history or subsequent chance events. In contrast, the evolution of cell size, a trait weakly correlated with fitness, was more strongly influenced by history and chance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
436
3
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 435 publications
(459 citation statements)
references
References 20 publications
19
436
3
1
Order By: Relevance
“…Microbial experiments have shown that selection is usually the most important driver of evolutionary change relative to history and chance after at least 200 generations of evolution in a novel environment [23][24][25][26][27][28]. Similar results have been obtained in sexual and initially diverse experimental populations of Drosophila after 20-30 generations [29,30].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Microbial experiments have shown that selection is usually the most important driver of evolutionary change relative to history and chance after at least 200 generations of evolution in a novel environment [23][24][25][26][27][28]. Similar results have been obtained in sexual and initially diverse experimental populations of Drosophila after 20-30 generations [29,30].…”
Section: Introductionsupporting
confidence: 73%
“…Each sum of squares estimate was divided by the sum of all estimates to obtain the relative contribution of each factor. We prefer this method to alternative variance component-based approaches [23,26,29] since our design does not permit a full additive partition of variation using these methods. Nevertheless, a variance component analysis of our data produced similar results.…”
Section: (C) Fitness Assaymentioning
confidence: 99%
“…The ¢tness reversion may be the more important e¡ect if the environment does not change but, if the environment should change, then the latent e¡ects of the original and compensatory mutations may be more important (e.g. Travisano et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Diversity is the product of three fundamental evolutionary influences: adaptation, chance, and history (Travisano et al 1995a). There is an intense debate in biology regarding the role that each of these factors plays in the evolutionary trajectories of organisms (Conway Morris 2003, Gould and Lewontin 1979, Mayr 1983, Lauder 1981, 1982, and we can ask the same question regarding the evolutionary paths taken by different cultures.…”
Section: Historicitymentioning
confidence: 99%